WORKSHOP ON EARLY DETECTION OF CONGENITAL DISORDERS FOR KNOWLEDGE UPDATE AND IMPROVEMENT OF PRIMARY HEALTH CARE PERSONNEL IN PROBOLINGGO CITY - Bella Amanda; Rimbun; Zakiyatul Faizah; Tri Hartini Yuliawati; Puguh Setyo Nugroho; Yuni Hisbiyah (Jurnal Layanan Masyarakat, 2023)
Congenital disorders are a group of rare diseases and one of the health problems that are often overlooked. Congenital disorder needs to get more attention because it can affect the quality of life of the patient and the affected family. Because of its impact on the patient's quality of life in the future, early detection is needed to be able to provide early intervention and minimize long-term effects. Doctors who work in primary health facilities have an important role in early detection of congenital abnormalities in the community. They are one of the first health workers visited by the community when they have questions and complaints about certain diseases. Improvement and update of knowledge for health workers is very important as an effort to reduce mortality and morbidity caused by congenital abnormalities. This community service is carried out by holding training activities for early detection of congenital abnormalities aimed at doctors who work in primary health care facilities. Increased knowledge of community service participants showed significant results (p <0.0001), which is expected to play an active role in early detection of congenital abnormalities in the people of Probolinggo City in the future.